The Contested Terrain of Historical Memory in Contemporary Mississippi - Nan Elizabeth WOODRUFF (E-REA)
Recently, black and white Mississippians have sought to confront and redress their history by forming interracial coalitions in communities where horrendous crimes occurred; by holding public debates over historical symbols surrounding the Confederacy, slavery, and civil rights; by attempting to reopen old civil rights murder cases; and by working to change the history curriculum in the public schools. The contemporary struggles over memory and history in Mississippi reflect conflicting black and white interpretations of the past. Many white Mississippians interested in acknowledging the history of the civil rights movement have yet to link that history with interpretations of slavery and the Civil War. They have yet to understand that an acknowledgment of the history of segregation and massive resistance to the civil rights movement requires a different interpretation of slavery and the Civil War.